Core components of a rehabilitation program in pediatric cardiac disease - Ubeda Tikkanen, Ana; Vova, Joshua; Holman, Lainie; Chrisman, Maddie; Clarkson, Kristin; Santiago, Rachel; Schonberger, Lisa; White, Kelsey; Badaly, Daryaneh; Gauthier, Naomi; Pham, Tam Dan N.; Britt, Jolie J.; et al. (Frontiers in Pediatrics, 2023)
There is increasing effort in both the inpatient and outpatient setting to improve care, function, and quality of life for children with congenital heart disease, and to decrease complications. As the mortality rates of surgical procedures for congenital heart disease decrease, improvement in perioperative morbidity and quality of life have become key metrics of quality of care. Quality of life and function in patients with congenital heart disease can be affected by multiple factors: the underlying heart condition, cardiac surgery, complications, and medical treatment. Some of the functional areas affected are motor abilities, exercise capacity, feeding, speech, cognition, and psychosocial adjustment. Rehabilitation interventions aim to enhance and restore functional ability and quality of life for those with physical impairments or disabilities. Interventions such as exercise training have been extensively evaluated in adults with acquired heart disease, and rehabilitation interventions for pediatric patients with congenital heart disease have similar potential to improve perioperative morbidity and quality of life. However, literature regarding the pediatric population is limited. We have gathered a multidisciplinary team of experts from major institutions to create evidence- and practice-based guidelines for pediatric cardiac rehabilitation programs in both inpatient and outpatient settings. To improve the quality of life of pediatric patients with congenital heart disease, we propose the use of individualized multidisciplinary rehabilitation programs that include: medical management; nursing care; rehabilitation equipment; physical, occupational, speech, and feeding therapies; and exercise training.